2012
DOI: 10.1111/j.1447-0594.2011.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated ischemic stroke is associated with elevated d‐dimer and fibrin degradation product levels in acute ischemic stroke with advanced cancer

Abstract: In acute ischemic stroke, the cancer-associated ischemic stroke is associated with elevated D-dimer and fibrin degradation products, even after controlling hypertension, hyperlipidemia and advanced cancer (clinical stage IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 16 publications
5
43
0
1
Order By: Relevance
“…10 Cancer patients with cryptogenic stroke have higher D-dimer levels and more frequently infarcts located in multiple vascular territories than patients with stroke associated with other pathogenesis. [11][12][13] The frequency of traditional ischemic stroke risk factors among cancer patients differs between studies. 10,13 Little is known about cancer among young and middle-aged patients with ischemic stroke.…”
mentioning
confidence: 99%
“…10 Cancer patients with cryptogenic stroke have higher D-dimer levels and more frequently infarcts located in multiple vascular territories than patients with stroke associated with other pathogenesis. [11][12][13] The frequency of traditional ischemic stroke risk factors among cancer patients differs between studies. 10,13 Little is known about cancer among young and middle-aged patients with ischemic stroke.…”
mentioning
confidence: 99%
“…These results suggest that patients with multiple lesions may have had occult cancer. 21 Moreover, it is possible that late-stage cancer may possibly influence D-dimer levels 20 or ischemic lesion patterns, 7 although we did not collect detailed information regarding patient cancer histories. The second major finding was the association of the presence of multiple infarcts and long-term stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Additionally, D-dimer levels are closely associated with cancer-associated stroke. 7,20 Several studies have shown that cancer-associated stroke may correlate with multiple ischemic lesion patterns. 7,21 Herein, our findings showed that patients with multiple lesions had higher rates for the history of cancer than patients with single or scattered lesions (16.9% versus 9.7%; P=0.120).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако сочетание данной симптоматики с измененными показа-телями крови и данными о наличии тромбоза являются сигналом для дообследования па-циента. Помимо этого, универсальными мар-керами любого ракового процесса являются повышение фибриногена, С-реактивного бел-ка, D-димера [8,9].…”
unclassified